Patogênese dos carcinomas de células escamosas alimentares associados ao consumo de Pteridium aquilinum em bovinos - Masuda, Eduardo Kenji (2010)
It is believed that papilloma formation is critical to pathogenesis of the upper digestive tract (UDT) squamous cell carcinomas (SCCs) in cattle, the so called papilloma-carcinoma syndrome. Due to the maintenance of papillomas for long periods of time in the UDT, due to immunosuppressive agents in bracken fern (Pteridium aquilinum), the keratinocytes of papilloma become target for carcinogens to promote carcinomatous transformation. Many evidences of the papilloma-carcinoma syndrome were observed in vitro. However, they have not been totally proved in vivo. The objectives of this study were therefore to assess key aspects of the pathogenesis of SCCs of the UDT in cattle naturally grazing in Pteridium aquilinum for long periods of time. For this, 168 initial epithelial lesions of the UDT were evaluated in 60 cattle with alimentary SCCs from areas with bracken fern. Developed papillomas had yielded more than 50% of the studied papillomas, with some in the growing phase (18.5%) and some carcinomatous transformation of papillomas (18.5%). A few papillomas were in regression (9%). The carcinomatous transformation of papillomas may represent morphological evidence of the need for papilloma formation in the development of alimentary SCCs. However, 72 squamous intraepithelial lesions (SILs) were also present in these bovines. Most SILs (70%) were moderate to severe dysplastic lesions and carcinomas in situ, with a significant amount of SCCs in an early stage of development. In humans, similar lesions are found in patients who chronically abuse of alcohol/tobacco. The SILs in the aerodigestive tract of humans are potentially malignant and can evolve to SCCs. The SILs of cattle in this study may therefore represent an alternative pathway for the development of SCCs in the UDT, without the necessity of carcinomatous transformation of papilloma to SCCs. The papillomatous origin of alimentary SCCs was also assessed by immunohistochemistry. Thirty SCCs of the cranial region of the UDT (including the base of tongue, pharynx/oropharynx and epiglottis) were evaluated about the acinar or ductal salivary origin using an anticytokeratin 7/8 antibody specific for simple epithelium. From the 30 SCCs examined, nine had morphological evidences of neoplastic transformation from a salivary duct. One of them was confirmed by immunohistochemistry to be of salivary origin. As papillomavirus requires a stratified epithelium for the formation of the papilloma, a confirmative SCCs from a simple salivary duct suggests that there is also no need of a papilloma to the development of SCCs of the UDT in cattle chronically grazing on bracken fern. In parallel, the degree of immunosuppression by lymphopenia, supposedly necessary for the maintenance of papillomas in the UDT, was evaluated in spontaneous cases of SCCs in the UDT of cattle. Alimentary papillomatosis was observed in all 40 cases studied. However, immunosuppression by lymphopenia was uncommon (three cases) and was not related to the degree of papillomatosis. The absence of lymphopenia in cattle with alimentary papillomatosis indicates that the mechanisms for maintenance of papilloma are not related to the amount of circulating lymphocytes. In conclusion, this study demonstrated an alternative route for the pathogenesis of SCCs in the UDT of cattle chronically poisoned by bracken fern and that the alimentary papillomatosis, observed in such cases, is not associated with lymphopenia.